Reproductive concerns and its correlation with fear of recurrence and level of family support in patients of childbearing age with gynecologic malignancies - Xinying He; Ying Wu; Yaqing Zhou; Qin Chen; Xuping Li; Xuemei Fan; Chengjun Xia; Jiao Ma; Jing Han; Xue Han (BMC, 2024)
Abstract Background To discuss the current status of reproductive concerns and its correlation with fear of recurrence and level of family support in patients of childbearing age with gynecologic malignancies. Methods A convenient sampling method was used to enroll 188 patients with gynecologic malignancies in Nanjing Maternity and Child Health Care Hospital, Nanjing Drum Tower Hospital, General Hospital of Ningxia Medical University, and Haian Hospital of Traditional Chinese Medicine Affiliated to Nanjing University of Chinese Medicine from September 2022 to April 2023. Patients were assessed using general information questionnaire, Reproductive Concerns After Cancer Scale (RCAC), Fear of Cancer Recurrence Inventory (FCRI) questionnaire, and Perceived Social Support-Family (PSS-FA) Scale. Results Among patients of childbearing age with gynecologic malignancies, the total RCAC score was (54.35 ± 7.52), indicating a moderate level of reproductive concerns. Patients scored (20.98 ± 4.51) on FCRI, implying a moderate level of fear of recurrence. The PSS-FA score was (9.57 ± 2.76), denoting a moderate level of family support. The total score and each dimensional score of RCAC were positively correlated with FCRI total score (P < 0.05), and negatively correlated with PSS-FA total score (P < 0.05). Fear of recurrence, family support level, number of children, educational background, treatment modality, and fertility intention were influencing factors for reproductive concerns in patients of childbearing age with gynecologic malignancies (all P < 0.05). Conclusion The reproductive concerns, fear of recurrence and family support are all at moderate levels in patients of childbearing age with gynecologic malignancies, and reproductive concerns are positively correlated with fear of recurrence and negatively correlated with family support.